Pengaruh metode Inkuiri Terhadap Hasil Belajar Siswa (Studi Kuasi Eksperimen Pada Mata Pelajaran Matematika Kelas IV di Sekolah Dasar Negeri Indrapuri Kecamatan Tapung Kabupaten Kampar) - Joni Joni; Suratno Suratno (LPPI Yayasan Almahmudi bin Dahlan, 2023)
The purpose of the research was to determine and analyze the effect of the inquiry method on student learning outcomes in grade IV mathematics at Indrapuri Public Elementary School, Tapung District, Kampar Regency. The research was d0ne on 64 students as research objects which were divided into an experimental class and a control class. The research method uses a quasi-experimental method with a data collection tool in the form of an objective test. The data obtained were analyzed using a paired sample t-test. The results of the study concluded that the application of the inquiry method had an effect on student learning outcomes in math class IV at Indrapuri State Elementary School (SDN), Tapung District, Kampar Regency. Thus it can be suggested that the inquiry method can be applied as an alternative learning method in elementary schools.